Increasing Windows security by hardening PC configurations - Martín Zamora Pablo; Kwiatek Michal; Nicolas Bippus Vincent; Cruz Elejalde Eneko (EPJ Web of Conferences, 2019)
Over 8000 Windows PCs are actively used on the CERN site for tasks ranging from controlling the accelerator facilities to processing invoices. PCs are managed through CERN's Computer Management Framework and Group Policies, with configurations deployed based on machine sets and a lot of autonomy left to the end-users. While the generic central configuration works well for the majority of the users, a specific hardened PC configuration is now provided for users who require stronger resilience against external attacks. This paper describes the technical choices and configurations involved and discusses the effectiveness of the hardened PC approach.